The Dharma master Chŏngsan of Won Buddhism : analects and writings - Chŏngsan, 1900-1961 (SUNY series in Korean studies., 2012)
The first English translations of the writings of Chŏngsan (1900-62), who codified the central doctrines of Won Buddhism.